Homo Deus: A Brief History of Tomorrow - Yuval Noah Harari (Vintage, 2017)
n a healthy, prosperous and harmonious world, mankind will turn our attention to our desire for eternal youth and happiness, and that these pursuits could ironically bring an end to our species. In the book, he examines our past, present and future, and highlights some difficult questions and choices that could shape our collective future.